FGF2 Affects Parkinson’s Disease-Associated Molecular Networks Through Exosomal Rab8b/Rab31 - Kumar, Rohit; Donakonda, Sainitin; Müller, Stephan A.; Bötzel, Kai; Höglinger, Günter U.; Koeglsperger, Thomas (Frontiers in Genetics, 2020)
Ras-associated binding (Rab) proteins are small GTPases that regulate the trafficking of membrane components during endocytosis and exocytosis including the release of extracellular vesicles (EVs). Parkinson’s disease (PD) is one of the most prevalent neurodegenerative disorder in the elderly population, where pathological proteins such as alpha-synuclein (α-Syn) are transmitted in EVs from one neuron to another neuron and ultimately across brain regions, thereby facilitating the spreading of pathology. We recently demonstrated fibroblast growth factor-2 (FGF2) to enhance the release of EVs and delineated the proteomic signature of FGF2-triggered EVs in cultured primary hippocampal neurons. Out of 235 significantly upregulated proteins, we found that FGF2 specifically enriched EVs for the two Rab-family members Rab8b and Rab31. Consequently, we investigated the interactions of Rab8b and Rab31 using a network analysis approach in order to estimate the global influence of their enrichment in EVs. To achieve this, we have demarcated a protein-protein interaction network (PPiN) for these Rabs and identified the proteins associated with PD in various cellular components of the central nervous system (CNS), in different brain regions, and in the enteric nervous system (ENS). A total of 126 direct or indirect interactions were reported for two Rab candidates out of which 114 are Rab8b interactions and 54 are Rab31 interactions, ultimately resulting in an individual interaction score (IS) of 90.48% and 42.86%, respectively. Conclusively these results for the first time demonstrate the relevance of FGF2-induced Rab-enrichment in EVs and its potential to regulate PD pathophysiology.